Immunosuppressive mechanisms of oncofetal reprogramming in the tumor microenvironment: implications in immunotherapy response. (26th April 2023) - Currenti, Jennifer; Mishra, Archita; Wallace, Michael; George, Jacob; Sharma, Ankur
Abstract : Both fetal and tumor tissue microenvironments display immunosuppressive features characterized by the presence of specific immunomodulatory stromal and immune cell populations. Recently, we discovered shared microenvironments between hepatocellular carcinoma (HCC) and fetal tissues and described this phenomenon as an oncofetal ecosystem. This ecosystem includes fetal-like immune (macrophage) and stromal (endothelial) cells within the tumor microenvironment (TME). This discovery highlights reciprocal interactions between fetal-like macrophages and T cells which result in the orchestration of an immunosuppressive TME. Importantly, VEGF-A protein expression by tumor cells and fetal-like macrophages plays an important role in oncofetal reprogramming of the TME in HCCs. Interestingly, recent clinical data indicate that blocking VEGF-A or CTLA4 alongside PD-L1 is effective in treating advanced HCC. Consequently, some immunotherapies may target and rely on oncofetal cells for clinical responsiveness. This understanding provides exciting opportunities to utilize oncofetal niche characteristics as biomarkers of immunotherapy response in HCC and might also have validity for predicting responses to immunotherapy in other cancers. In this review, we explore the immunosuppressive mechanisms and interactions of oncofetal cells in the TME of HCC and their potential implications for immunotherapy response.